Algorithms for the computation of all Mathieu functions of integer orders. - Alhargan, Fayez A.
The article presents methods for the computation of all Mathieu functions of integer order, which cover a large range of n and h; previous algorithms were limited to small values of n. The algorithms are given in sufficient detail to enable straightforward implementation. The algorithms can handle a large range of the order n (0-200) and the parameter h (0-4n).
Keywords: Hill's determinant; Mathieu characteristic determinant; Mathieu characteristic numbers; Mathieu coefficients; Mathieu differential equation; Mathieu functions; Elliptic cordinates; Wave equation